2015
DOI: 10.1142/s0129065715500276
|View full text |Cite
|
Sign up to set email alerts
|

Altered Structural and Functional Feature of Striato-Cortical Circuit in Benign Epilepsy with Centrotemporal Spikes

Abstract: Benign epilepsy with centrotemporal spikes (BECT) is the most common form of childhood idiopathic focal epilepsy syndrome. We investigated quantitative evidence regarding brain morphology and functional connectivity features to provide insight into the neuroanatomical foundation of this disorder, using high resolution T1-weighted magnetic resonance imaging (MRI) and resting state functional MRI in 21 patients with BECT and in 20 healthy children. The functional connectivity analysis, seeded at the regions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 61 publications
6
50
1
Order By: Relevance
“…In previous studies, decreased FC has often been reported in patients with different types of epilepsy, [26,32,33] suggesting that the epileptiform activity interrupts the functional interactions of the brain. Interestingly, more obvious FC was observed in the patients with BECTS than in the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, decreased FC has often been reported in patients with different types of epilepsy, [26,32,33] suggesting that the epileptiform activity interrupts the functional interactions of the brain. Interestingly, more obvious FC was observed in the patients with BECTS than in the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Prior works focusing on the subcortical development of BECTS reported selective putamen hypertrophy among the basal ganglia structures (Garcia‐Ramos et al, ; Lin et al, ). In addition, a recent resting‐state fMRI study has shown decreased connections among the motor network and fronto‐striatal loop in BECTS (Luo et al, ). Aberrant functional interaction between the motor cortex and language areas was also demonstrated in children with rolandic epilepsy (Besseling et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, interictal epileptic discharges also lead to the transient cognitive impairment (Hommet et al, 2006). Using functional magnetic resonance imaging (fMRI), many of the studies on focal epilepsy demonstrated the abnormality in subcortical network, default mode network, hippocampal network, and so on Liao et al (2011) and Luo et al (2015). Similarly, the altered functional networks covering cortical and subcortical structures were observed in patients with IGE (Luo et al, 2012a; Dong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%